Malignant melanoma of the mandibular gingiva: A rare occurrence - Reddy BVR; Sridhar G; Anuradha C; Chandrasekhar P; Lingamaneni K (Wolters Kluwer Medknow Publications, 2010)
Primary mucosal malignant melanoma of the oral cavity is a rare tumor. It accounts for only 0.2-8% of all malignant melanomas. This malignancy commonly affects male subjects and is more frequently seen on the hard palate and maxillary gingiva. The peak age for diagnosis of oral melanoma is between 55 and 65 years. A biopsy is required to establish a diagnosis. Ablative surgery with tumor-free margins remains the treatment of choice. It has a much poorer prognosis than its counterpart on the skin. Here, we present a case of malignant melanoma of the mandibular lingual gingiva in a 55-year-old male patient. Immunohistochemistry and special stains were conducted for confirmatory diagnosis.